2013
DOI: 10.5539/ijps.v5n3p98
|View full text |Cite
|
Sign up to set email alerts
|

Mammography Screening within the Context of the Theory of Planned Behavior: The Role of Personality Traits and Personal Factors

Abstract: The present study examined the associations between optimism, personal characteristics and theory of planned behavior (TPB) components for mammography screening. Most of the results were in line with TPB which proposed that intention would be the most proximal determinant of a behavior and the effects of other factors including attitudes and perceived behavioral control on behavior would be mediated through intention. However, a number of demographic and health-related factors, including age and a previous ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…While early detection of breast cancer via mammography screening ultimately reduces breast cancer mortality in the target population (Nelson, 2009; Sarkeala et al., 2008), participation rates vary drastically from 6% to 80% (Basu et al., 2018). To improve participation in mammography screening, it is important to identify the factors related to participation via validated models of human behavior (Griva et al., 2013). Two models often used to study participation in mammography screening are the Health Belief Model (HBM) and the Theory of Planned Behavior (TPB) (Savage & Clarke, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While early detection of breast cancer via mammography screening ultimately reduces breast cancer mortality in the target population (Nelson, 2009; Sarkeala et al., 2008), participation rates vary drastically from 6% to 80% (Basu et al., 2018). To improve participation in mammography screening, it is important to identify the factors related to participation via validated models of human behavior (Griva et al., 2013). Two models often used to study participation in mammography screening are the Health Belief Model (HBM) and the Theory of Planned Behavior (TPB) (Savage & Clarke, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Griva et al [ 49 ] discussed the role of personality factors in the acceptance of mammography screening. In this previous study, the authors included optimism as a factor in governing acceptance of mammography screening; however, the results indicated that optimism did not affect mammography screening behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Personality also can be described in terms of these two dimensions, but two additional dimensions shed light on the concept of personality separate from those two ( Tellegen and Waller, 2008 ; Matz and Harari, 2020 ). Individuals respond to vulnerabilities viewed as traits which triggered their personal behavior ( Griva et al, 2013 ). Several studies have shown that research has been done on international students’ personality characteristics and psychosocial adjustment associations ( Brunsting et al, 2018 ; Bulgan and Çiftçi, 2018 ; Xie et al, 2021 ).…”
Section: Psychosocial Factorsmentioning
confidence: 99%